Experimental Substantiation of Special Training Simulators Application during Canoeists` Training Process - Lukashevich, D. (Sporto Mokslas-Sport Science, 2017)
This article develops the problems, associated with the complexity and difficulty of the process of canoe athletes` motorconditioning parameters assessment. The possibility of special rowing machines appliance in the training process at the stage of preparatory period is revealed in here.